حاشية المُدُرْنِ على نزهة النَّظَر من الحديث الصَّحيح إلى الإسناد - Arran, İyad (Fatih Sultan Mehmet Vakıf Üniversitesi, 2023)
الحمد لله رب العالمي، والصَّ لاة والسَّ لام على نبييِنا محمَّ د وعلى آله وصحبه أجمعي وبعد: فإنَّ علم مصطلح الحديث يعَُدُّ من العلوم المهمَّة بي العلوم الإسلامية، وقد اهتمَّ العلماء الأجلَّاء بهذا العلم اهتماماً كبيراً، ووضعوا له القواعد والضَّوابط التي تحفظ السُّنة النَّبويَّة، وتحميها من التَّحرييف والتَّزييف. نزُْهَةُ النَّظَرِ في توضيح نُُْبَةِ الفِكَر في مصطلح أهل « ومن أحسن هذا التَّصانيف، وأنفعها كتاب للحافظ ابن حجر العسقلاني المتوفى سنة ،» الأثر 852 ه/ 1372 م رحمه الله، فهو على اختصاره حوى على أهم أصولِ علم مصطلح الحديث وقواعده وفن ونه، ولقد تناوَلَهُ العلماء شَرْحاً وتَدْرِيساً، والطُّلابُ حِ فْظاً وفَهْماً، ووُضِعَتْ عليه الشُّروح والحواشي والمنظومات. ومن الحواشي النَّافعة التي وُضِعَتْ على هذا المتن العظيم، حاشِية الشَّيخ محمَّد بن مصطفى المُدُرْنِي ، وهو عالم من علماء عهد الدَّولة العثمانية، المتوفى بعد سنة 1136 ه رحمه الله، فقد جمع مح يِ شي ها بي ثناياها مع ما أضاف إليها من فوائ د لطيفة، فكانت ،» نزُْهَةُ النَّظَرِ « زبدة بعض الحواشي والشُّروح التي كُتِبَتْ على حاشية نافعة ماتعة. وقد أكرمني الله تعالى بتحقيق ودراسة القسم الثَّاني منها على ثلاث نسخ خطيَّة للكتاب، لتكون رسالة مقدَّمة لنيل درجة الماجستير في العلوم الإسلامية بجامعة السُّلطان محمَّد الفاتح الوقفية في إسطنبول، وذلك من بداية التَّعريف بالحديث الصَّحيح إلى نهاية موضوع الإسناد. الكلمات المفتاحية: نزهة النظر، نُبة الفكر، حاشية، ابن حجر، المُدُرْنِي .

Âlemlerin Rabbi Allah'a hamdolsun. Rasûllerin Efendisi Peygamberimiz Muhammed Mustafa’ya, ehl-i beytine ve ashâbına salât ve selâm olsun. Hadis Istılahları İlmi, İslam alimlerinin büyük önem verdikleri, Peygamberimiz’in sünnetini onu tahriften korumak üzere kurallar ve esasalar koydukları ilimlerden biridir Bu konuda telif edilen değerli ve meşhur eserlerden biri, Hafız İbn Hacer el- Askalanî'nin (ö. 852/1449) "Nuzhatü’n-nazar fi tavdîhi Nuhbeti’l-fiker fi mustalahi ehli’l-eser" adlı eseridir. Veciz bir eser olmasına rağmen hadis terminolojisinin en önemli usûl, kural ve ölçülerini içermektedir. Bu özlü eser, ilim erbabı tarafından medreselerde ders kitabı olarak okutulmuş, talebeler tarafından ezberlenmiş ve üzerine şerhler, haşiyeler ve manzumeler yazılmıştır. Bu metin üzerine yazılan önemli haşiyeler arasında Osmanlı devri âlimlerinden Muhammed bin Mustafa el-Mudurnî’nin (ö.1136 hicrî yılı sonrası) "Haşiyetü Nuzheti’n-nazar” adlı haşiyesi ilmî, değerli ve önemli bir haşiyedir. Bu haşiye üzerine henüz akademik bir çalışma yapılmamıştır. İstanbul'da Fatih Sultan Mehmet Vakıf Üniversitesi'nde Temel İslâm Bilimleri alanında yüksek lisans çalışması olarak sunduğum bu tezde kitabın sadece (sahih hadisin tarifinden isnad konusunun sonuna kadar olan) ikinci kısmını üç yazma nüshaya dayanarak tahkik edip değerlendirme yapma imkânı veren Rabbime hamdolsun.

Praise be to Allah, the Lord of the worlds, and peace and blessings be upon our Prophet Muhammad, his family and companions. Hadith terminology is one of the important sciences of Islamic law, and distinguished scholars gave great importance to this science, and established rules and controls that protected the Sunnah of the Prophet and protected him from falsification and fraud. One of the best and most useful of these compilations (classifications) is "Nuzhat al- Nazar Fi Tavdeeh Nuhbat al-Fiker fi Mustalah Ahl al-Eser" by Hafiz Ibn Hajar al-Askalani, who died in 852 Hijri/1449 Gregorian (May Allah have mercy on him). Despite its brevity, it contains hadith terminology’s the most important methods,rules and arts. Despite its brevity, this hadith terminology contains the most important methods, rules and arts of science. Scholars dealt with it in tafsir and teaching,students memorized and understood it, and commentaries, annotations (footnotes) and systems were put on it. Among the useful annotations (footnotes) included in this great text are the footnotes of Sheikh Mohammed bin Mustafa Al Mudurni (who died after 1136 Hijri/1724 Gregorian), one of the scholars of the Ottoman period - may Allah have mercy on him. He combined some of the annotations (footnotes) and explanations written on "Nuzhat al-nazar" into its folds with the nice benefits it added, thus making it a useful and enjoyable annotation (footnote). Allah Almighty honored me with his examination of the three written copies of the second part of the book as a thesis submitted to the Fatih Sultan Mehmet Vakif University in Istanbul for a master's degree in Basic Islamic Sciences. And this is from the beginning of the introduction of the true hadith to the end of the subject of citation here.
Mudurnî’nin Nüzhetü’n-Nazar Haşiyesi’nin Sahih Hadis’ten İsnad Konusuna Kadar Olan İkinci Bölümünün Tahkik ve Değerlendirilmesi
Hashiyatu al-Mudurny Ala Nuzha an-Nazar, from al-Sahih to al-Isnad, Edition Qritique and Evaluation
Keywords: نزهة النظر; نُبة الفكر; حاشية; ابن حجر; المُدُرْنِي; Nuzhatü’n-Nazar; Nuhbeti’l-Fiker; Haşiyet; İbn Hacer; el-Mudurnî; Nuzhat al-Nazar; Nuhbat al-Fiker; Footnote; Al-Mudurni